Case Report: Gemcitabine-induced membranoproliferative glomerulonephritis with immune complexes in a patient with metastatic pancreatic cancer - Abdelhakeem, Ahmed; Baker, Lyle; Amin, Md. Shahrier; Babiker, Hani; Aslam, Nabeel; Majeed, Umair (Frontiers in Medicine, 2025)
Gemcitabine is a widely used chemotherapeutic agent for pancreatic adenocarcinoma, that is associated with rare but serious renal complications including thrombotic microangiopathy (TMA). We report a unique case of biopsy-proven membranoproliferative glomerulonephritis (MPGN) with immune complex deposition in a woman receiving gemcitabine for metastatic pancreatic cancer. She developed new-onset hypertension, proteinuria, microscopic hematuria, and progressive renal dysfunction shortly following initiation of gemcitabine. Extensive autoimmune, complement, paraprotein, and viral serologies were unremarkable aside from a low haptoglobin. Kidney biopsy revealed an MPGN pattern with immune deposits. Gemcitabine was discontinued, and the patient was treated with corticosteroids and kidney-protective therapies targeting blood pressure and proteinuria reduction. Her proteinuria decreased significantly, and her renal function returned back to baseline. This case highlights a rare manifestation of gemcitabine-induced nephrotoxicity with immune complex MPGN, suggesting a possible novel mechanism of drug-associated glomerular injury.